Metabolic and Cardiovascular Benefits of Apple and Apple-Derived Products: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Kim, Sun Jo; Anh, Nguyen Hoang; Jung, Cheol Woon; Long, Nguyen Phuoc; Park, Seongoh; Cho, Young Hyun; Yoon, Young Cheol; Lee, Eun Goo; Kim, Mina; Son, Eui Young; Kim, Tae Ha; Deng, Yingqian; et al. (Frontiers in Nutrition, 2022)
Background: Quantitative evidence of the metabolic and cardiovascular effects of apples (Malus domestica) is lacking in interventional studies. This study aimed to summarize the available evidence of the beneficial effects of apples and apple-derived products (ADPs) on metabolic and cardiovascular markers. Methods: Peer-reviewed randomized controlled trials (RCTs) were identified from four databases on May 3, 2021 and regularly updated until the end of May 2021. Demographic characteristics, intervention types, and evaluation parameters were extracted. A meta-analysis on the mean difference of change scores was conducted on commonly presented outcomes in the RCTs. Results: The metabolic and cardiovascular effects of diverse regimens, including whole apple, apple extract, and apple juice, were examined in 18 eligible RCTs. Nine common evaluation outcomes were eventually introduced to the meta-analysis, including total cholesterol (TC), low-density lipoprotein (LDL), high-density lipoprotein (HDL), triglyceride, glucose, insulin, C-reactive protein, and systolic/diastolic blood pressures. The levels of TC (-2.69 mg/dL; 95% CI: -5.43, 0.04 mg/dL) and LDL (-2.80 mg/dL; 95% CI: -5.78, 0.17 mg/dL) showed a non-significant decreasing tendency after at least a week of apple consumption. Further subgroup analysis, particularly, a comparison with placebo as a control, showed a significant reduction in TC and LDL levels. When stratified by the baseline level, subjects with high TC and LDL level were shown to have more benefits from the apple intake. Intriguingly, apple and ADPs significantly reduced HDL levels to a small extent (-1.04 mg/dL; 95% CI: -1.79, -0.29 mg/dL). The other markers were mostly unaffected by the intervention. Conclusions: Our investigation revealed that apples could improve blood cholesterol levels.